Protocol for preservation, hand sectioning and staining for quantification of root anatomical traits - Hernández, Urys; Cardoso, Juan Andrés (CGIAR Initiative on Livestock and Climate, 2023)
Understanding plant adaptation to edaphic factors requires knowledge of plant traits and responses of the root system. Root anatomy is a good indicator of the strategies and limitations of plants to its environment, yet, it is underutilized in plant breeding programs. The following was written to serve as a guide for the identification and quantification of root anatomical traits.